2006
DOI: 10.2307/40035905
|View full text |Cite
|
Sign up to set email alerts
|

Bear's Journey and the Study of Ritual in Archaeology

Abstract: This paper considers the archaeological study of ritual and explores the interrelationships that exist between ideologically meaningful accounts of ritual and the material representations of ritual practice that remain for archaeological evaluation. Specifically, the paper addresses the development and antiquity of the Midewiwin ritual, a ceremonial complex that is known historically throughout the Great Lakes region. The serendipitous discovery of a linkage between the Mide origin tale of Bear's Journey and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…We have argued for the regional ceremonial importance of enclosures previously (5,39). Some recent research emphasizes the importance of enclosures as locally embedded features, noting that, although they may share a circular form, they each have their own distinct layout and material signatures, reducing prospects that they had broader regional orientations (30,35).…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…We have argued for the regional ceremonial importance of enclosures previously (5,39). Some recent research emphasizes the importance of enclosures as locally embedded features, noting that, although they may share a circular form, they each have their own distinct layout and material signatures, reducing prospects that they had broader regional orientations (30,35).…”
Section: Resultsmentioning
confidence: 86%
“…We have argued that, within this context, dual needs arose to (i) maximize and extend the use life of local resources and (ii) increase interaction with other communities occupying different territories and resource bases (5,39,43,44). As introduced above, we have suggested that the construction of mounds filled local needs and that the construction of enclosures filled more regional ones.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…As identified by their spatial locations and stratigraphic details, these unusual constructions of decomposed and burned cow dung, soils, and material culture are interpreted as not just enormous middens but instead as products of episodic ritual practice that visually reinforced sociosymbolic meanings; only analysis at a regional scale could identify this pattern. In south-central Ohio, Bernardini's (2004) examination of Hopewell earthworks distinguishes the ''referential meaning'' of individual monuments from their ''experiential meaning,'' suggesting that the earthworks were part of a single regional landscape maintained through ceremonial action rather than the separate creations of autonomous villages (see also Howey and O'Shea 2006). Massive ditches found in southern Benin, West Africa also take on new meaning when examined through the lens of landscape archaeology (Norman and Kelly 2004).…”
Section: Landscape Archaeologymentioning
confidence: 95%